2022
DOI: 10.1021/acsami.2c19916
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Turn-On Fluorescent Metal–Organic Framework for Detecting Trace Water in Organic Solvents Based on the Excited-State Intramolecular Proton Transfer Mechanism

Abstract: Simple, fast, and sensitive detection of trace water in organic solvents is an urgent requirement for chemical industries. Herein, combining the unusual excited-state intramolecular proton transfer (ESIPT) mechanism with the effective strategy of pore space partition, for the first time, we construct a powerful fluorescent metal−organic framework (SNNU-301) probe with excellent water stability. The SNNU-301 probe shows a remarkable performance for turn-on ESIPT-based fluorescence response to water in nine comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…When the DHT linker is taking part in the MOF structure, the carboxylate groups are anchored to the Zr metal atoms, because the ESIPT reaction is less favored, and therefore, the enol species can emit light. The observation of two emission bands corresponding to enol and keto tautomers of DHT linkers have been previously described for other DHT-based MOFs. ,, Moreover, we have observed that the relative intensity ratio between these two emission bands depends on the excitation wavelength (Figure ). When the UiO-66-(OH) 2 MOF is photoexcited with higher energies (lower wavelengths), the emission of the keto tautomer (525 nm) is enhanced.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…When the DHT linker is taking part in the MOF structure, the carboxylate groups are anchored to the Zr metal atoms, because the ESIPT reaction is less favored, and therefore, the enol species can emit light. The observation of two emission bands corresponding to enol and keto tautomers of DHT linkers have been previously described for other DHT-based MOFs. ,, Moreover, we have observed that the relative intensity ratio between these two emission bands depends on the excitation wavelength (Figure ). When the UiO-66-(OH) 2 MOF is photoexcited with higher energies (lower wavelengths), the emission of the keto tautomer (525 nm) is enhanced.…”
Section: Resultssupporting
confidence: 83%
“…This is followed by a charge reorganization, leading to the formation of the keto tautomer, whose emission maximum falls in the region of ∼525 nm (as previously demonstrated), reflecting the increase in intensity of this band. Similar mechanism has been proposed to explain the response of DHT-based MOFs to the presence of different chemicals in solution such as water or F – . ,, The photoluminescence quantum yield of UiO-66-(OH) 2 is weak, 0.34%, and it increases by ∼5 (1.60%) and ∼2 (0.55%) times in the presence of HCl and Et 3 N, respectively. This further corroborates the turn-on sensing mechanism.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…To date, according to the types of ESIPT sites, most studied ESIPT ligands to construct metal–organic supramolecular materials can be divided into derivatives of azoles, quinolines, pyrimidines, salicylates, etc. And the general metal ions can include the d 10 -type ions (Zn 2+ , Cd 2+ , In 3+ ), ,, ,,,, alkali-earth ions (Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ ), ,,, Zr 4+ ions, , rare earth ions (Ln 3+ ), ,, etc. Basically, the strategy for the construction of ESIPT metal–organic supramolecular materials must consider the following three principles.…”
Section: Introductionmentioning
confidence: 99%
“…In general, metal–organic optical functional materials have remarkable advantages, including adjustable frame structures, convenient assembly process, and diverse luminescent mechanisms. With the fast development of modern characterization techniques and supramolecular self-assembly research, studies based on the design and application of ESIPT metal–organic optical materials have been attracting considerable interest. ,, The construction and PL regulation of ESIPT-attributed metal–organic materials with strong photothermal stability, spectral response specificity and excellent optical performance is considered to an important direction for the development of new ESIPT materials. ,, …”
Section: Introductionmentioning
confidence: 99%